2019
DOI: 10.1371/journal.pone.0212089
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the protective effects of plant extracts against amyloid-beta peptide-induced toxicity in human neuroblastoma SH-SY5Y cells

Abstract: Alzheimer’s disease (AD) is the most common form of dementia and has no cure. Therapeutic strategies focusing on the reduction of oxidative stress, modulation of amyloid-beta (Aβ) toxicity and inhibition of tau protein hyperphosphorylation are warranted to avoid the development and progression of AD. The aim of this study was to screen the crude extracts (CEs) and ethyl-acetate fractions (EAFs) of Guazuma ulmifolia , Limonium brasiliense , Paullinia cup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 64 publications
2
19
0
Order By: Relevance
“…However, it has been suggested that inhibition of H. pylori induced gastric inflammation associated with oxidative stress is considered as one of the promising approaches to prevent carcinogenesis (Cao et al, 2007). This statement is in agreement with our results where pyrogallol is an antioxidant (Kang et al, 2011;Li, 2012) and reported to be an anti tumor agent in breast cancer and neuroblastoma model (Nemec et al, 2016;Sereia et al, 2019). Our current data suggests that anti colon tumor efficacy of pyrogallol could be due to scavenging of free radicals produced by H. pylori induced inflammation associated carcinogenesis in mice.…”
Section: Discussionsupporting
confidence: 92%
“…However, it has been suggested that inhibition of H. pylori induced gastric inflammation associated with oxidative stress is considered as one of the promising approaches to prevent carcinogenesis (Cao et al, 2007). This statement is in agreement with our results where pyrogallol is an antioxidant (Kang et al, 2011;Li, 2012) and reported to be an anti tumor agent in breast cancer and neuroblastoma model (Nemec et al, 2016;Sereia et al, 2019). Our current data suggests that anti colon tumor efficacy of pyrogallol could be due to scavenging of free radicals produced by H. pylori induced inflammation associated carcinogenesis in mice.…”
Section: Discussionsupporting
confidence: 92%
“…The CD-MEKC methodology present several advantages over traditional chromatographic approaches. [36,37] Not only does it allow a rapid flavonoid fingerprinting of the extract, but also enables the evaluation of the antioxidant capacity of each compound upon the reaction with DPPH * in the context of the whole plant extract, considering the potential synergy and antagonism among flavonoids. Consequently, this approach most closely resembles what actually takes place in a real sample when tested as an antioxidant.…”
Section: Inhibition Of Uva-induced Skin CLmentioning
confidence: 99%
“…It contains very high levels of caffeine as well as polyphenols such as catechins and epicatechins [ 103 ]. Recently, in vitro antioxidant assay done on a variety of Brazilian herb extracts, including from guarana seeds, have been reported [ 104 ]. Moreover, the antioxidant and anti-ageing potential of guarana seed, together with its protective effect on neurodegenerative diseases, has been well documented [ 105 , 106 , 107 ].…”
Section: Free Radicals and Oxidative Damage To Biomoleculesmentioning
confidence: 99%